Diverse bryophyte mesofossils from the Triassic of Antarctica. (29th November 2013) - Bomfleur, Benjamin; Klymiuk, Ashley A.; Taylor, Edith L.; Taylor, Thomas N.; Gulbranson, Erik L.; Isbell, John L.
<x xml:space="preserve">Abstract</x> Compared with the fossil record of vascular plants, bryophyte fossils are rare; this circumstance is probably related to a lower preservation potential compared with that of vascular plants. We searched for bryophyte remains in extensive collections of plant‐fossil assemblages from the Triassic of Antarctica and identified three assemblages with surprisingly well‐preserved bryophyte fossils. Although most bryophyte remains are too fragmented to conclusively place them in a detailed systematic context, they exhibit features sufficient to suggest the presence of at least four types of leafy bryophytes and two orders of thallose liverworts (Pallaviciniales and Metzgeriales) in the high‐latitude Triassic ecosystems of Antarctica. The leafy bryophytes exhibit combinations of morphological features (e.g. keeled and entire‐margined, ecostate leaves with elongated cells) that today occur in only a few small, systematically isolated groups, but were common among Palaeozoic and especially Mesozoic bryophytes. The diverse morphologies of the bryophyte fossils add further support to previous hypotheses that during warmer periods in the Earth's history, bryophyte vegetation may have been particularly rich and diverse in high‐latitude regions. Through analysis of the sedimentology and taphonomy of these assemblages, we identify a combination of key factors that may explain the preservation of bryophyte fossils in these deposits: (1) punctuated, high‐energetic sedimentary events causing traumatic removal and incorporation of bryophytes into sediment‐laden flood waters; (2) limited transport distance, and short period of suspension, followed by rapid settling and burial as a result of a rapidly decelerating flow discharging into a floodplain environment; and (3) early‐diagenetic cementation with iron hydroxides in locally anoxic zones of the organic‐rich, muddy substrate.